THE EXTENSIVE READING AS A WAY OF TEACHING SPANISH - Syngayivska, Ganna (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
At present, the promotion of reading the literary text is aimed at forming the reading habit in students and integrating them in the different socio-cultural contexts where they interact; motivate them to experience reading activity from pleasure, to develop reading behavior in them. Owning this type of communicative activity, a person understands everything he reads, and responds adequately to what he has read, converting his thoughts in response. Reading any text in a foreign language and answering questions about the text or expressing their opinion about the read, the student learns the skills of monologue speech. In this article, the author considers the importance of extensive reading in the study and teaching of Spanish as a Foreign Language or any other foreign language, presents approaches to teaching reading that can be used in reading and parsing any text, introduces activities to be used in an extensive reading program, and analyzes the reading practices in the students of the 2nd year of E/LE at the Taras Shevchenko National University of Kyiv. The benefits of extensive reading include gains in reading and writing competence, growth of vocabulary, and increases in self-respect and motivation of students. Reading books can be a good way to acquire new vocabulary, see grammar in action and develop understanding of a language. It is important that the books are interesting to students and at a level appropriate to their reading ability.________________References:• Cabrera Pernia, Madelaine, and Alexis Benancio Álvarez Cortés. 2021. “Los Beneficios de La Lectura Extensiva Para El Profesor En Formación de Español-Literatura. (Revisión). Roca: Revista Científico - Educaciones de La Provincia de Granma17 (1): 97–116. URL: https://dialnet.unirioja.es/servlet/ articulo?codigo= 8212151.• Cervantes, CVC Centro Virtual. n.d. “CVC. Diccionario de Términos Clave de ELE. Lectura Extensiva.” Cvc.cervantes.es. URL: https://cvc.cervantes.es/ensenanza/biblioteca_ele/diccio_ ele/diccionario/lecturaextensiva.htm.• Day, Richard R, and Julian Bamford. 1998. Extensive Reading in the Second Language Classroom. Cambridge, U.K. ; New York: Cambridge University Press.• Day, Richard R. 2002. “Top Ten Principles for Teaching Extensive Reading.” Reading in a Foreign Language14 (2): 136–141.• “EFL Extensive Reading Instruction.” 2019. Kyoto-Su.ac.jp. 2019. URL: https://www.cc.kyoto-su.ac.jp/~trobb/sussrobb.html.• Elley, Warwick B., and Francis Mangubhai. 1983. “The Impact of Reading on Second Language Learning.” Reading Research Quarterly19 (1): 53. URL: https://doi.org/10.2307/747337.• “Extensive Reading: What Is It? Why Bother? | JALT Publications.” n.d. Jalt-Publications.org. URL: https://jalt-publications.org/tlt/articles/2132-extensive-reading-what-it-why-bother.• Kembo, Jane. "Reading: Encouraging and maintaining individual extensive reading." In English Teaching Forum 31 (2) (1993): 36–38.• Madelaine Cabrera Pernia, Alexis Álvarez Cortés, Adell A Barzaga, and Mayelin Aranda Velázquez. “La Lingüística Textual Como Vía de Análisis Para Comprender Las Lecturas Extensivas. (Revisión).” Roca: Revista Científico - Educaciones de La Provincia de Granma 16 (1) (2020): 1383–1393. URL: https://dialnet.unirioja.es/ descarga/articulo/8372418.pdf.• “Marco Común Europeo de Referencia Para Las Lenguas: Aprendizaje, Enseñanza, Evaluación. Volumen Complementario – Publicaciones – Ministerio de Educación Y Formación Profesional.” n.d. Sede.educacion.gob.es. URL: https://sede.educacion.gob.es/publiventa/marco-comun-europeo-de-referencia-para-las-lenguas-aprendizaje-ensenanza-evaluacion-volumen-complementario/lenguas-europa/25397.• Mason, Beniko, and Stephen Krashen. “Extensive Reading in English as a Foreign Language.” System25 (1) (1997): 91–102. URL: https://doi.org/10.1016/s0346-251x(96)00063-2.• Uden, J. “The Extensive Reading Foundation’s Guide to Extensive Reading.” ELT Journal67 (2) (2013): 270–272. URL: https://doi.org/10.1093/elt/cct010.
Keywords: reading; extensive reading; extensive reading activities; methods of teaching reading; types of reading